Development and Evaluation of a Web-Based Paediatric Drug Information System for Germany - Julia Zahn; Stefan Wimmer; Wolfgang Rödle; Irmgard Toni; Brita Sedlmayr; Hans-Ulrich Prokosch; Wolfgang Rascher; Antje Neubert (MDPI AG, 2021)
Background: Off-label use is frequent in paediatrics but that does not necessarily mean that the risk-benefit ratio is negative. Nevertheless, evidence-based data is essential for safe drug therapy. In Germany, there is no publicly available compendium providing transparent, evidence-based information for paediatric pharmacotherapy to date. This work describes the development of a web-based paediatric drug information system (PDIS) for Germany and its evaluation by health care professionals (HCP). Methods: Since 2012, a PDIS is being developed by the authors and is supported by the Federal Ministry of Health since 2016. Dosing recommendations were established based on systematic literature reviews and subsequent evaluation by clinical experts. The prototype was evaluated by HCP. Based on the results, the further development was concluded. Results: 92% of HCP believed that the PDIS could improve the quality of prescribing, as currently available information is deficient. Besides the license and formulations, dosing recommendations were the most relevant modules. A dosage calculator was the most wanted improvement. To facilitate sustainability of future development, a collaboration with the Dutch Kinderformularium was established. As of 2021, the database will be available to German HCP. Conclusion: The fundamentals for a German PDIS were established, and vital steps were taken towards successful continuation.